2010
DOI: 10.1097/rhu.0b013e3181fe8b37
|View full text |Cite
|
Sign up to set email alerts
|

Observational Cross-Sectional Study Revealing Less Aggressive Treatment in Japanese Elderly Than Nonelderly Patients With Rheumatoid Arthritis

Abstract: Elderly patients with RA receive less aggressive treatment than nonelderly patients with RA, despite laboratory evidence for poorly controlled disease status among the elderly. The use of a less aggressive regimen could be attributed to the higher prevalence of complications and problems. Therefore, the elderly with RA should be considered a different patient population from the viewpoint of treatment and be administered specialized medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Consistent with known clinical practices and the genetic and clinical characteristics of patients with RA in Japan [22][23][24], there were some expected differences in patient characteristics at baseline for the Japanese subpopulations compared with the overall populations. For example, lower body weight and lower methotrexate doses were seen in Japan in all four studies [18][19][20][21]; the maximum approved weekly methotrexate dose for RA in Japan is 16 mg [25].…”
Section: Discussionmentioning
confidence: 57%
“…Consistent with known clinical practices and the genetic and clinical characteristics of patients with RA in Japan [22][23][24], there were some expected differences in patient characteristics at baseline for the Japanese subpopulations compared with the overall populations. For example, lower body weight and lower methotrexate doses were seen in Japan in all four studies [18][19][20][21]; the maximum approved weekly methotrexate dose for RA in Japan is 16 mg [25].…”
Section: Discussionmentioning
confidence: 57%
“…In addition, in clinical practice, patients with RA in Japan are often prescribed lower doses of MTX (< 9 mg per week in average doses 14,15 , until recently) compared with patients in the United States (> 15 mg per week 16 ), which may theoretically affect the response to, and tolerability of, concomitant RA medication. Therefore, investigating the efficacy and safety of baricitinib in an Asian population is important before initiating phase III studies.…”
Section: Rheumatologymentioning
confidence: 99%
“…[21][22][23] The differences in first-line therapy between our two age groups are consistent with earlier reports. In a registry study reported in 2006, onset of RA after 60 years of age was 9 In general, the risk of adverse drug events increases with advancing age, due to the gradual accumulation of comorbidities such as heart failure and kidney dysfunction, as well as to the ageassociated decline in immune function. Also, drugs are often less effective in older patients.…”
Section: Discussionmentioning
confidence: 99%
“…These differences suggest a greater risk of adverse drug effects that may lead physicians to limit the aggressiveness of the treatments they prescribe to older patients. 8,9 Although driven by concern over patient safety, this attitude may deprive older patients of optimal disease control and quality of life. Several trials comparing patients younger than 65 years and 65 years or over showed similar drug safety profiles and treatment discontinuation rates.…”
Section: Introductionmentioning
confidence: 99%